Construction of Sustainable Frugal Innovations Index for the Agriculture Sector - Nhokovedzo, Simbarashe (International Journal of Sustainable Agricultural Research, 2021)
The proliferation of agriculture innovations require stakeholders to have an accurate measurement scale to screen and select the best inventions for returns maximisation. Agriculture has evolved to become a scientific business hence the need for scientific measurements of agro-innovations and their consequences. The concepts of sustainability and frugality, hence sustainable frugal innovations are trending themes in agriculture. High quality scientific measures of these innovations remain scarce. The purpose of this study has been to develop a Sustainable Frugal Innovations index for use in the agriculture sector. A data collection instrument derived from sustainability and frugality constructs was developed and administered to 450 Agriculture experts across Zimbabwe. Twenty-five (25) constructs were extracted through Confirmatory Factor Analysis (CFA), validated and analysed, culminating in a composite Sustainable Frugal Innovation Index.